Real‐Time and Wireless Assessment of Adherence to Antiretroviral Therapy With Co‐Encapsulated Ingestion Sensor in HIV‐Infected Patients: A Pilot Study. Issue 1 (15th October 2019) - Daar, Eric S.; Rosen, Marc I.; Wang, Yan; Siqueiros, Lisa; Shen, Jie; Guerrero, Mario; Xiong, Di; Dao, John; Young, Todd; Corado, Katya; Fletcher, Courtney V.; Liu, Honghu
Abstract : Adherence with antiretroviral therapy is important for preventing disease progression and HIV transmission. The co‐encapsulated pill sensor system sends a signal through a cutaneous patch and allows real‐time monitoring of pill ingestion. A 16‐week pilot study used a sensor system in 15 HIV‐infected individuals with real‐time monitoring of pill‐taking with a personalized short message system text. System acceptability was assessed by survey at weeks 4, 8, 12, and 16. Follow‐up occurred in 80% of subjects through 8 weeks. The system effectively collected measures of pill ingestion, which triggered text message reminders. Only 2 of 14 participants stated that co‐encapsulated pills were "unable to take" or "poorly tolerated." At least 75% of respondents stated at each visit that the patch was very or somewhat comfortable. With regard to text message reminders, only 10–15% of the participants at any visit did not find the messages to be helpful. Larger studies will define the utility of this system to assess antiretroviral adherence relative to standard measures.